Pengenalan dan Pelatihan Coding dan Konsep Dasar Pemrograman Anak Berkebutuhan Khusus Tunarungu SLB Nurul Ikhsan Ngadiluwih - Lutfina, Erba Lutfina; Iqlima Zahari; Wildan Mahmud; Natalinda Pamungkas; Kenza Amelia Putri Anwarri (Magistrorum et Scholarium: Jurnal Pengabdian Masyarakat, 2024)
Various efforts have been made to overcome problems related to digital literacy to form independence and life skills for deaf students. SLB Nurul Ikhsan requires non-formal education for deaf students as preparation for finding work or continuing to a higher level of school. This community service activity aims to improve the digital literacy skills of deaf students by introducing programming languages ​​through coding. Deaf students are trained to use coding to sharpen logic by creating simple games using the SilentTeacher and Scratch applications. The activity results showed that the deaf students successfully developed a simple game on the Scratch application. This activity was well received by the participants because it achieved the participant satisfaction target of 84%.